Long‐term urological complications after conservative local treatment (surgery and brachytherapy) in children with bladder–prostate rhabdomyosarcoma: A single‐team experience. Issue 8 (6th January 2022) - Akkary, Rezkalla; Guérin, Florent; Chargari, Cyrus; Jochault, Loic; Audry, Georges; Pio, Luca; Minard‐Colin, Veronique; Haie‐Meder, Christine; Martelli, Hélène
Abstract: Background: Outcome of children with bladder–prostate rhabdomyosarcoma (RMS) has improved with multimodal therapies, including surgery and/or radiotherapy for local treatment. Our aim was to report long‐term urological complications after a conservative approach combining conservative surgery and brachytherapy. Patients and methods: Eighty‐six patients, free of disease, were retrospectively reviewed. Symptoms related to urinary tract obstruction, incontinence, infection, and lithiasis were reported and graded according to the Common Terminology Criteria for Adverse Events (CTCAE) classification. Only symptomatic patients underwent urodynamic studies. Risk factors for complications were analyzed. Results: There were 76 males and 10 females. The median follow‐up was 6.3 years (18 months to 24 years). Complications occurred after a median follow‐up of 5 years (0–21). Twenty‐two patients (26%) had long‐term urological complications. Urinary tract obstruction was found in 15 patients (17%) and urinary incontinence in 14 patients (16%). Recurrent urinary tract infection occurred in four patients and urinary lithiasis in four (5%). The underlying physiopathology included bladder dysfunction in 15 patients (17%), urethral stenosis in six (7%), and ureterovesical junction stenosis in five (6%). On univariate analysis, posterior bladder wall dissection ( p = .001), bladder neck trigone dissection ( p = .010), and partial prostatectomy ( p = .023) were significantly associated with an increased risk of bladder dysfunction; on multivariate analysis, only age ≤2 years ( p = .028) at operation and posterior bladder wall dissection ( p = .006) were found to be significant. Conclusion: The conservative surgical approach combined with brachytherapy for bladder–prostate RMS leads to long‐term urological complications in 26% of survivors. Optimizing brachytherapy doses for young children and establishing a clear and long‐term follow‐up protocol could help to reduce these complications.